Influence of growing direction on seed yield and quality in bottle gourd (Lagenaria siceraria) - SHARMA, RAJESH KUMAR; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2016)
The present investigation was carried out to study the influence of growing direction, i.e. E-W and N-S direction on growth, flowering, fruit set, seed yield and quality attributes of bottle gourd (Lagenaria siceraria (Mol.) Stand) at SPU, IARI, New Delhi during kharif 2014. The results revealed that growth characters i.e. vine length, leaves/vine, leaf area, leaf nodes/vine, primary laterals and leaves on primary laterals had significantly higher in E-W direction at 45 DAS and leaves/vine, leaf area, leaf nodes/vine, leaves on primary laterals and secondary laterals at 55 DAS. The reduction in number of days to anthesis of first male flower and female flower in E-W direction as compared to N-S direction was observed. Significantly more number of male flowers and less female flower per plant were recorded in E-W direction along with less sex ratio. The fruit development attributes, i.e. fruit set/vine, fruit developed to maturity, fruit weight, fruit length, fruit width, cavity volume and thickness of fruit wall were reported significantly higher in EW direction. Seed yield attributes, i.e. seed yield/fruit, seed yield/vine and seed yield/acre were found significantly higher in E-W direction but number of total seed, filled seed and unfilled seed per fruit showed at par among the direction of sowing. Similarly seed quality attributes, viz. seedling length (43.49cm), seedling dry weight (0.687 g), vigour index I (4247.37) and VI-II (67.13), seed coat weight and embryo weight were recorded significantly superior in E-W direction than N-S direction. Germination (%) and electrical conductivity of seed leachate showed at par performance among the both the direction of sowing.